2013
DOI: 10.1016/j.foodchem.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury in rice by MSFIA and cold vapour atomic fluorescence spectrometry

Abstract: In the present paper the use of a MSFIA system for determination of mercury in rice by cold vapour atomic fluorescence spectrometry (CV AFS) is proposed. The sample digestion is performed in a microwave oven using nitric acid and hydrogen peroxide. The experimental conditions for vapour generation were determined using a full two-level factorial design involving the following factors: nitric acid and tin chloride concentrations and sample flow rate. Employing the conditions optimised, the method allows the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The majority of recent studies on methylation in rice paddies have examined contaminated systems (Rothenberg et al 2014), which are beyond the scope of this paper. However, methylation has been found to occur in non-contaminated rice cultivation sites around the world including Brazil (da Silva et al 2010;Batista et al 2012;Silva et al 2012), China (Rothenberg et al 2011), and Spain (da Silva et al 2013). The use of stable isotope tracers recently confirmed that MeHg produced in saturated soils is subsequently observed in the plant's rice grains (Strickman and Mitchell 2017), suggesting that the prevalence of methylation in rice paddies is a significant concern due to its potential to cause mercury poisoning directly through a common staple food source.…”
Section: Inundated Environmentsmentioning
confidence: 99%
“…The majority of recent studies on methylation in rice paddies have examined contaminated systems (Rothenberg et al 2014), which are beyond the scope of this paper. However, methylation has been found to occur in non-contaminated rice cultivation sites around the world including Brazil (da Silva et al 2010;Batista et al 2012;Silva et al 2012), China (Rothenberg et al 2011), and Spain (da Silva et al 2013). The use of stable isotope tracers recently confirmed that MeHg produced in saturated soils is subsequently observed in the plant's rice grains (Strickman and Mitchell 2017), suggesting that the prevalence of methylation in rice paddies is a significant concern due to its potential to cause mercury poisoning directly through a common staple food source.…”
Section: Inundated Environmentsmentioning
confidence: 99%
“…e high-level toxicity of mercury depends on its chemical forms such as the form of methylmercury has more toxicity than the form of elemental mercury [1][2][3]. When mercury enters the food chains, its concentration deposits and increases in the food change, affecting the life of many animals [4,5]. In the past, mercury was used in several applications such as dentistry, industry, and mining.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, quantification of mercury in environment and living organisms is usually performed by electrochemistry [6], inductively coupled plasma mass spectrometry (ICP-MS) [7], atomic fluorescence spectrometry (AFS) [8][9][10], atomic absorption spectrometry (AAS) [11,12], and high performance liquid chromatography with detection by ICP-MS or AFS [13,14]. Although these techniques provide low detection limit and are suitable for monitoring ultratrace mercury, the requirement of sophisticated analytical instrumentation, well trained personnel, or complex processes make such techniques difficult to implement for field detection.…”
Section: Introductionmentioning
confidence: 99%